Bacteriological Profile and Antibiotic Susceptibility Pattern of Isolates of Wound Infection In Children Visiting Kanti Children Hospital (Tribhuvan University Journal of Microbiology, 2020)
Objectives: The objectives of this study was to isolate and identify the bacterial etiological agent of wound infection and explore the status of methicillin-resistant Staphylococcus aureus ( MRSA), multidrug Resistant (MDR) and extended spectrum β-lactamase (ESBL) producers’ strains in clinical specimens and to find the antibiotic susceptibility pattern.Methods: A prospective cross sectional study design was conducted from period of February 2014 to October 2014 at Kanti Children Hospital, Kathmandu. The organisms were isolated and identified from pus sample by standard microbiological methods. Antimicrobial susceptibility test was performed by modified the Kirby Bauer disc diffusion method to evaluate the status of MRSA and MDR. ESBL detection was performed by the combined disc diffusion method.Results: Out of 365 specimens collected between the age group below < 2 to 15 years, 210 (57.73%) samples from male patients and 155 (42.47%) from female patients. In the total samples processed, Gram-positive organisms were found to be more prevalent in which Staphylococcus aureus accounts for 135(47.20%), followed by P. aeruginosa 62 (21.67%), E. coli 29 (10.20%), K. pneumoniae 27 (9.44%), Acinetobacter spp. 20 (6.70%), P. vulgaris 7 (2.44%) and CoNS 6 (2.10%). Among the S. aureus isolates, 29 (21.48%) were found MRSA. Of the total Gram-negative organisms isolated, 74 (51.03%) were MDR and 14 (100%) ESBL producer, (P